Creating market opportunities in rural areas through the development of a brand that conveys sustainable and environmental values. (April 2020) - Escribano, M.; Gaspar, P.; Mesias, F.J.
Abstract: The dehesa is the most widespread agroforestry system within the European Union and provides an important set of provisioning, regulating, and cultural ecosystem services. However, these systems have been in decline for a number of years, to a great extent because of their lack of profitability. Among the different options available to add value to agroforestry systems such as the dehesa and make them more profitable, the development of brands that would help consumers identify the products they generate is one of the most promising alternatives. In this way, the value of dehesa products would be enhanced and the revenue obtained from them increased. However, whilst such products are locally appreciated, a challenge exists in so far as neither national nor international consumers are able to identify dehesa products and therefore they are not willing to pay a premium for them. In this context, the creation of an umbrella brand covering the products derived from the dehesa is considered to be useful for boosting revenues in dehesa systems. This piece of research used a qualitative approach combining discussion groups with projective techniques during a series of workshops to identify relevant branding concepts and imagery for dehesa products. The findings showed that the term dehesa is recognised and appreciated by consumers, although it is associated with traditional and expensive products. It was also found that in order to make the brand more attractive to more consumers -especially younger consumers-additional concepts such as "sustainability" and "socially-responsible" production need to be incorporated in the branding. Imagery displaying forests and other environmental motifs were found to be the strongest graphical means of depicting these concepts within the brand design. It is considered that these findings could help enhance the demand and revenues associated with dehesa products and sustain the benefits they provide for the environment and for society. Highlights: Development of a brand covering agroforestry products could help enhance revenues in extensive farms. The brand could help consumers identify the benefits farms provide for environment and society. The brand needs to include additional concepts such as "sustainability" and "socially-responsible". Imagery displaying forests and other environmental motifs should be included in the design.